2013
DOI: 10.1111/jop.12130
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of new aloe vera‐ and myrrh‐based oral mucoadhesive gels in the management of minor recurrent aphthous stomatitis: a randomized, double‐blind, vehicle‐controlled study

Abstract: The new formulated aloe- and myrrh-based gels proved to be effective in topical management of MiRAS. Aloe was superior in decreasing ulcer size, erythema, and exudation; whereas myrrh resulted in more pain reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 20 publications
1
84
0
7
Order By: Relevance
“…The 'pain reduction' time (to VAS 2) in the control group was comparable to that reported in other studies focused on the treatment of aphthous lesions using gels and pastes (23)(24)(25). Mansour et al (25) reported the time needed for the 'pain reduction' in the group of patients treated by a myrrh and aloe mucoadhesive gel between 4 and 5 days of treatment; Babaee et al (23) reported it to be about 4 days (treatment using myrtle oral paste), while Jiang et al (24) with their oral paste containing a fibroblast growth factor reached the pain reduction after 6 days of treatment.…”
Section: Discussionsupporting
confidence: 84%
“…The 'pain reduction' time (to VAS 2) in the control group was comparable to that reported in other studies focused on the treatment of aphthous lesions using gels and pastes (23)(24)(25). Mansour et al (25) reported the time needed for the 'pain reduction' in the group of patients treated by a myrrh and aloe mucoadhesive gel between 4 and 5 days of treatment; Babaee et al (23) reported it to be about 4 days (treatment using myrtle oral paste), while Jiang et al (24) with their oral paste containing a fibroblast growth factor reached the pain reduction after 6 days of treatment.…”
Section: Discussionsupporting
confidence: 84%
“…[43] A. vera gel is used as an adjuvant treatment of oral submucous fibrosis. [172] A. vera -and myrrh-based oral mucoadhesive gels are used in the management of minor recurrent aphthous stomatitis. [173] Nimesulide-incorporated A. vera transemulgel is used to relieve pain.…”
Section: Antidiabetesmentioning
confidence: 99%
“…Para pacientes que presentaban úlceras recurrente oral, se estudió el uso de Aloe vera (Bhalang et al, 2013) y Rhizophora mangle (de Armas et al, 2005), reportándose efectos positivos en la disminución de los signos clínicos y sintomatología. En la misma línea, Mansour et al (2014) evaluaron el uso de Aloe vera o Commiphora myrrha en úlceras recurrente oral, reportando que Aloe vera mejoró signos clínicos (eritema, exudado) mientras que el uso de Commiphora myrrha disminuyó la sintomatología dolorosa. Así también, para lesiones de liquen plano erosivo y leucoplasia erosiva, se ha estudiado el uso de Lithospermum erythrorhizon (Zagorodnyaya et al, 2013); para Liquen plano erosivo y no erosivo, el uso de Vitis vinifera (Rivarola de Gutierrez et al, 2014); y para Liquen plano atrófico y erosivo, el uso de Curcuma longa, (Chainani-Wu et al, 2011) reportando todos efectos positivos en los parámetros clínicos de las lesiones y en la sintomatología relatada por los pacientes.…”
Section: Lesiones Orales Ulcerativas (Uro Lpe Lce)unclassified